Histórias das mulheres privadas de liberdade em Manaus: vidas marcadas pela pobreza, violência e abandono - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The increase in the number of incarcerated women has been increasing exponentially in Brazil, between 2004 and 2014, the rate of female incarceration has increased by 300%. In Amazonas the reality is not different, the percentage of growth of this prison follow-up was of 99%. Data from the Ministry of Justice indicate that most of these women are arrested for involvement in drug trafficking, 58% of them, while only 23% of men are imprisoned for this criminal type. In the Amazon 54% of them are imprisoned for this crime. In recent years, a number of scholarly researches have emerged on female imprisonment, a large part of which is dedicated to analyzing the issue of prison conditions, the practice of motherhood in prison and other matters related to prison daily life, there are still few who seek to discuss the issue The insertion of women in the "world of crime". In Manaus we did not find any research that fomented the question. With the purpose of apprehending female crime from its social relations and thus delineating some determinants for the insertion of women in crime, an empirical research of a qualitative approach was carried out with women condemned to custodial sentences in Manaus. The approach of the participants was the life history. Of the 106 convicted prisoners serving sentences in the closed and semi-open regimes in that capital, 9 were willing to participate in this study, 6 were convicted of drug trafficking and 3 were assaulted out of that total, only two had never had any involvement in the sale of Drugs. The interviews were recorded, transcribed and analyzed in the light of sociological theories. The study revealed that the involvement of women in crime has strong social inequality relations and the transformations that have occurred in the world of work and in family relations with productive restructuring and the emergence of neoliberalism. In the meantime work in the drug trade and other illicit activities that generate income is becoming naturalized as any other form of reproduction of life are activities as precarious and dangerous, as thousands of others in the informal market conduct sometimes offer better gain And the possibility of reconciling care with offspring and work. In order to slow down the rate of female incarceration, it is therefore imperative to think of other forms of coping with crime, as well as building prisons and investments in repressive policies, as well as rethinking our current drug policy.
Keywords: Mulheres presas em Manaus; Criminalidade Feminina; Tráfico de drogas; Desigualdade Social; CIÊNCIAS HUMANAS: SOCIOLOGIA